Respuesta :
let other one be (x,y)
We know midpoint formula
[tex]\boxed{\sf (x,y)=\left(\dfrac{x_1+x_2}{2},\dfrac{y_1+y_2}{2}\right)}[/tex]
[tex]\\ \sf\longmapsto (6,-4)=\left(\dfrac{13+x}{2},\dfrac{-2+y}{2}\right)[/tex]
[tex]\\ \sf\longmapsto \dfrac{13+x}{2}=6[/tex]
[tex]\\ \sf\longmapsto 13+x=12[/tex]
[tex]\\ \sf\longmapsto x=12-13[/tex]
[tex]\\ \sf\longmapsto x=-1[/tex]
And
[tex]\\ \sf\longmapsto \dfrac{-2+y}{2}=-4[/tex]
[tex]\\ \sf\longmapsto -2+y=-8[/tex]
[tex]\\ \sf\longmapsto y=-8+2[/tex]
[tex]\\ \sf\longmapsto y=-6[/tex]
Answer:
(- 1, - 6 )
Step-by-step explanation:
Given endpoints (x₁, y₁ ) and (x₂, y₂ ) then the midpoint is
( [tex]\frac{x_{1}+x_{2} }{2}[/tex] , [tex]\frac{y_{1}+y_{2} }{2}[/tex] ) ← midpoint formula
Use this formula on the endpoints and equate to the coordinates of the midpoint.
let the other endpoint = (x, y) , then
[tex]\frac{13+x}{2}[/tex] = 6 ( multiply both sides by 2 )
13 + x = 12 ( subtract 13 from both sides )
x = - 1
[tex]\frac{-2+y}{2}[/tex] = - 4 ( multiply both sides by 2 )
- 2 + y = - 8 ( add 2 to both sides )
y = - 6
The coordinates of the other endpoint are (- 1, - 6 )